Effect of the Nitrification Inhibitor 3,4-Dimethylpyrazole Phosphate on the Deep Placement of Nitrogen Fertilizers for Soybean Cultivation - Soshi Hatano; Yoichi Fujita; Yoshifumi Nagumo; Norikuni Ohtake; Kuni Sueyoshi; Yoshihiko Takahashi; Takashi Sato; Sayuri Tanabata; Kyoko Higuchi; Akihiro Saito; Takuji Ohyama (International Journal of Agronomy)
The deep placement of urea fertilizer (DMU) containing 1% (W/W) of the nitrification inhibitor 3,4-dimethylpyrazole phosphate (DMPP) on soybean growth and seed yield was as effective as those of the coated urea (CU) and lime nitrogen (LN) in a field research. The average seed yields were high in LN (464 g·m−2) and DMU (461 g·m−2) and relatively low in CU (405 g·m−2), U (396 g·m−2), and Cont (373 g·m−2) treatments. The accumulations of dry matter and nitrogen in soybean shoots were higher in the plants with deep placement of CU, LN, and DMU than U and Cont. The daily nitrogen fixation activity and daily nitrogen absorption rate were calculated based on the relative ureide method. Both nitrogen fixation activity and nitrogen absorption rate were higher in DMU, CU, and LN compared with control treatment, suggesting that the deep placement of DMU did not repress nitrogen fixation. Soil incubation test was performed using the same field soil with DMU, U, LN, and urea with DMPP 1%, 2%, and 4%. DMU inhibits nitrification similar to the pattern of LN until 8 weeks. The increasing DMPP concentration did not markedly increase the nitrification inhibition. From these results, it was concluded that urea fertilizer with 1% DMPP is efficient for deep placement of N fertilizer for soybean cultivation due to its lower price compared with CU and LN.